An Analysis of High Order Thinking Skills Aspects on the Assessment Instruments Environmental Change Topic for the 10th GradeSenior High School Students - Masyitoh Masyitoh; Yuni Ahda; Indra Hartanto; Rahmawati Darussyamsu (Universitas Negeri Padang, 2020)
High level learning ability (HOTS) is the ability of students to be critical and creative thinking skills. In 2013, students were required to be able to receive information and remember it, but students must be able to solve the problems they faced with the knowledge they needed. Based on observations, the instruments used by teachers are still at the level of C1-C3, while for high-level thinking abilities students must be able to think at the C4-C6 level. This study aims to analyze the ability of high-level thinking of students on material changes in the environment. The assessment instrument used is an instrument of assessment of high-level thinking ability that is valid, practical, reliable and has good quality items. The instrument is said to be valid if the instrument can measure what should be measured. The practicality of the assessment instrument depends on how easily the instrument is used to assess students' abilities. Reliable means that the instrument gives the same results when tested in the same group at different times. An instrument that has good quality items is an instrument that has a moderate level of difficulty and sufficient differentiation, good and very good. Based on the results of the test questions, the average value of students is 41.37 which is still categorized as low. The low level of students' high-level thinking skills can be improved by familiarizing students with higher-order thinking and using scientific learning models.